Development of Smart Apps Creator Media with IDEAL Approach to Improve Mathematics Problem Solving Ability in Elementary School - Ramadhani, Revita Helmalia Putri; Trimurtini, Trimurtini (FKIP Universitas Lampung, 2025)
Students' less-than-optimal ability to solve math problems is crucial in today's education. This research aims to develop Smart Apps Creator media with the IDEAL approach to improve students' ability to solve math problems. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects in the small-scale trial were 15 fourth-grade students of SDN Karangayu 03, while the large-scale trial was 27 fourth-grade students of SDN Karangayu 01. The initial data collection in this study involved documentation, interviews, questionnaires, and observations. The research instruments used include pretest and post-test to measure the effectiveness of the media, as well as expert validation to assess the feasibility of the developed media. The paired sample t-test analysis in the small group showed a t-count value of -19.587, smaller than the t-table value of 2.145, while in the large group, the t-count value obtained was -33.771, smaller than the t-table value of 2.056. This result shows a significant difference between both groups' pre-test and post-test results. The use of smart apps creator learning media with the IDEAL approach proved to be very effective in improving students' problem solving abilities. This is evidenced by an increase in pretest and post-test scores, with an N-gain test value in the small group of 0.69, which is included in the medium category, while in the large group, it is 0.83, which is included in the high category. Developing smart apps creator learning media with an IDEAL approach is valid, practical, and effective in improving students' mathematical problem-solving abilities. Keywords: learning media, smart apps creator, problem-solving, IDEAL.